Analisis Implementasi Aplikasi Sistem Keuangan Desa (Siskeudes) Terhadap Kinerja Pemerintah Desa Pada Pemerintahan Nagari Sandi Ulakan Kec. Ulakan Tapakih Kab. Padang Pariaman - Meidona, Syofria; Afrianti, Rini; Multama, Ilham; Erniza, Erniza (Al-Hijrah: Journal of Islamic Economics And Banking, 2024)
The aim of this research is to analyze the implementation of the Village Financial System (SISKEUDES) application in improving the performance of village officials. This research was conducted in Sandi Ulakan, Ulakan, Tapakih District. Where data collection is carried out by observation, interviews and documentation. The results of this research indicate that Sandi Ulakan Village has implemented the Village Financial System (SISKEUDES). Village financial management in Sandi Ulakan Village is in accordance with Standard Operating Procedures, namely Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 20 of 2018 concerning Village Financial Management. Village financial management in Sandi Ulakan Village includes planning, implementation, administration and reporting. Through research conducted, village financial management using the village financial system in Sandi Ulakan improves the performance of village officials .